2008
DOI: 10.1007/s10571-007-9234-1
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of High Voltage-activated Ca2+ Channels in GC Somatotropes After Long-term Exposure to Ghrelin and Growth Hormone Releasing Peptide-6

Abstract: Activation of the growth hormone (GH)-secretagogue receptor (GHS-R) by synthetic GH-releasing peptides (GHRP) or its endogenous ligand (ghrelin) stimulates GH release. Though much is known about the signal transduction underlying short-term regulation, there is far less information on mechanisms that produce long-term effects. In the current report, using whole-cell patch-clamp recordings, we assessed the long-term actions of such regulatory factors on voltage-activated Ca(2+) currents in GH-secreting cells de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 54 publications
(74 reference statements)
2
16
0
Order By: Relevance
“…An immunocytochemical study also suggested that pituicytes express Ca v 1.2, 2.1, 2.2, 2.3, and 3.1 subunits (108). In GH somatotrophs, ghrelin and GH-releasing peptide-6 enhanced the expression of the Ca v 1.3 pore-forming ␣-subunit (109). In L␤T2 gonadotrophs, leptin increases L-type Ca v channel expression and GnRH-stimulated LH release (110).…”
Section: Voltage-gated Ca 2؉ Channelsmentioning
confidence: 94%
“…An immunocytochemical study also suggested that pituicytes express Ca v 1.2, 2.1, 2.2, 2.3, and 3.1 subunits (108). In GH somatotrophs, ghrelin and GH-releasing peptide-6 enhanced the expression of the Ca v 1.3 pore-forming ␣-subunit (109). In L␤T2 gonadotrophs, leptin increases L-type Ca v channel expression and GnRH-stimulated LH release (110).…”
Section: Voltage-gated Ca 2؉ Channelsmentioning
confidence: 94%
“…channel expression was increased and Ca 2? channel activity was enhanced in GC cells by long-term treatment (96 h) with ghrelin and GHRP-6 [10]. There maybe difference between long-term and short-term treatments.…”
Section: Discussionmentioning
confidence: 95%
“…Dominguez et al reported that high voltage-activated Ca 2? channel activity was enhanced in GC rat somatotrope cell line after long-term treatment (96 h) of cells by ghrelin and GHRP-6 [10]. Short-term modification of Ca 2?…”
Section: Introductionmentioning
confidence: 95%
“…Though much is known about the signal transduction underlying short-term regulation, but there is far less information on mechanisms that produce long-term effects. Although the molecular mechanisms of GH release are ill defined, some studies have shown that GHS-R sustained activation may be linked to increased voltage-gated Ca 2+ channel surface expression, resulting in enhanced electrical and secretory activity in clonal pituitary somatotropes [9, 25]. This latter type of regulation is likely to play a role in long-lasting forms of plasticity in the pituitary gland [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, the upregulation of voltage-gated HVA L-type calcium channel (Ca v 1.3) [9] and an upregulation of voltage-gated Na + channels by long-term activation of the GHS-R in this cell line have been observed [8]. Likewise, in goldfish pituitary cells Ghrelin-induced GH release involves voltage-sensitive calcium channels [10, 11].…”
Section: Introductionmentioning
confidence: 93%